Network Plasticity Involved in the Spread of Neural Activity Within the Rhinal Cortices as Revealed by Voltage-Sensitive Dye Imaging in Mouse Brain Slices - Kajiwara, Riichi; Tominaga, Yoko; Tominaga, Takashi (Frontiers in Cellular Neuroscience, 2019)
The rhinal cortices, such as the perirhinal cortex (PC) and the entorhinal cortex (EC), are located within the bidirectional pathway between the neocortex and the hippocampus. Physiological studies indicate that the perirhinal transmission of neocortical inputs to the EC occurs at an extremely low probability, though many anatomical studies indicated strong connections exist in the pathway. Our previous study in rat brain slices indicated that an increase in excitability in deep layers of the PC/EC border initiated the neural activity transfer from the PC to the EC. In the present study, we hypothesized that such changes in network dynamics are not incidental observations but rather due to the plastic features of the perirhinal network, which links with the EC. To confirm this idea, we analyzed the network properties of neural transmission throughout the rhinal cortices and the plastic behavior of the network by performing a single-photon wide-field optical recording technique with a voltage-sensitive dye (VSD) in mouse brain slices of the PC, the EC, and the hippocampus. The low concentration of 4-aminopyridine (4-AP; 40 μM) enhanced neural activity in the PC, which eventually propagated to the EC via the deep layers of the PC/EC border. Interestingly, washout of 4-AP was unable to reverse entorhinal activation to the previous state. This change in the network property persisted for more than 1 h. This observation was not limited to the application of 4-AP. Burst stimulation to neurons in the perirhinal deep layers also induced the same change of network property. These results indicate the long-lasting modification of physiological connection between the PC and the EC, suggesting the existence of plasticity in the perirhinal-entorhinal network.